Comparing depression and sexual satisfaction in fertile and infertile couples - N Bahrami; N Sattarzadeh; F Ranjbar Koochaksariie; M Ghojazadeh (JRI, 2007)
Introduction: Some studies demonstrate that depression, stress, low self-esteem and sexual dissatisfaction may be psychological outcomes of infertility. Depression and sexual satisfaction may play a significant role in the life of infertile couples, their infertility treatment follow-ups and their hopefulness for the future. This study was done to determine and compare rates of depression and sexual satisfaction among infertile and fertile couples referring to Al-Zahra medical educational center in Tabriz during 2006. Materials & Methods: This was a comparative-descriptive study in which depression and sexual satisfaction rates were studied and compared in 150 randomly selected infertile versus 150 fertile couples. Data gathering was done by using a questionnaire with 3 parts 1) Demog-raphic characteristics, 2) Beck Depression Inventory (BDI) and 3) Larson′s standard question-naire for determining sexual satisfaction. The data gathered from this study were analyzed by SPSS software (Version 14) through calculations of descriptive statistical methods (Frequency, mean and standard deviation), tests of association (χ2 and correlation coefficient) and the mean difference tests (T-test for independent and paired groups plus one-way ANOVA). P<0.05 was considered significant. Results: The mean differences for depression between infertile and fertile men and women were significant, but for sexual satisfaction, they were not statistically significant. The mean difference for depression in infertile women was higher than that of their husbands′ but sexual satisfaction scores in men and women were not much different. Also, there was a negative correlation between sexual satisfaction and depression. Conclusion: Infertile couples need rigorous care and treatment for their psychological prob-lems. Active participation of infertile couples during treatment process and presence of psy-chiatrists and psychologists in the treatment of emotional and psychological problems of the couples are of great importance.
Keywords: Fertility, Infertility, Infertile couple, Psychology, Depression, Sexual satisfaction